Comparative analysis of technical and tactical preparedness Greco-Roman style wrestler at the Olympic Games-2008 and the Olympic Games-2012 - Tropin, Y. M. (Physical Education of Students, 2013)
The aim is to test preparedness of Greco-Roman style wrestlers. It is analysed battles of 41 wrestlers conqueror of the finals of the competition. Found that competition on the world stage in the Greco-Roman wrestling is high, the leader is constantly changing. It was determined that the effectiveness of the use of technology at the Olympic Games in 2008 is significantly higher (26%) than in the Olympic Games in 2012 revealed three weight groups: small (55 kg, 60 kg), medium (66 kg, 74 kg, 84 kg), heavy (96 kg, 120 kg). Found that in the Greco-Roman tendency to simplify the technology, increase the intensity of the match. It was revealed that at the Olympics in 2008 the performance indicator is higher than at the Olympic Games in 2012 in all weight groups. Found that the most informative for evaluating the technical and tactical capabilities fighters carries the final part of the competition, which is determined by the efficiency, effectiveness, technical arsenal.